Images of the child created by parenting websites - Kubiak-Szymborska, Ewa; Furtak, Olga (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The issues of the child (and also of childhood) are relatively often addressed in various publications, revealing the multiplicity of aspects and contexts of these categories. The aim of this text is to consider the „child” category in the context of the phenomenon of mediatization which, in particular, comes down to looking at it from the perspective of the most popular parenting websites. Both images with a positive emotional charge as well those with a negative and ambivalent one are discussed in the text. They do not exhaust the spectrum of images of the child, but comprise those that appear most often on these websites and constitute a certain „added value” to the images presented by other researchers, looking at the child from the perspective of TV series and television programmes, or commercials. The review and analysis of parenting websites indicate that in the vast majority they present the image of the child, defined in this text as a child at risk, regardless of whether this risk lies in the enormous mass of disease causative agents (highest frequency), or in other factors related to the care and upbringing of the child, and the circumstances and conditions in which they take place (lower frequency). It gives rise to specific consequences. On the one hand, exhibiting such an image provides parents with the necessary knowledge sensitizing them to all kinds of factors that mayturn out to be unfavourable to the child’s development while, on the other hand, creating such an image may result in parents’ excessive and unjustified fear of being a parent, or in being overprotective when caring for the child. Therefore, it is important to make parents aware of the fact that using parenting websites they should do so with caution and the necessary detachment from the information provided in them and, above all, keep common sense in assessing the content they come in contact with.
Keywords: child; mediatization; parenting websites; image